1998
DOI: 10.1002/etc.5620171017
|View full text |Cite
|
Sign up to set email alerts
|

In vitro induction of ethoxyresorufin‐O‐deethylase and porphyrins by halogenated aromatic hydrocarbons in avian primary hepatocytes

Abstract: Ethoxyresorufin‐O‐deethylase (EROD) and porphyrin induction responses of primary hepatocytes to halogenated aromatic hydrocarbons (HAHs) were examined in newly hatched domestic chickens, herring gulls, ring‐billed gulls, double‐crested cormorants, and Forster's terns. Concentration–response relationships were determined for both biochemical responses in hepatocyte preparations derived from individual avian livers (except for the tern). The choice of vehicle used to dose chicken hepatocytes greatly affected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 55 publications
7
33
0
Order By: Relevance
“…Although mammals have only a single AHR, birds have at least two AHR isoforms, AHR1 and AHR21011. Despite the evolutionary conservation of the AHR-mediated signaling pathway in birds, earlier in vitro and in vivo studies have reported large interspecies differences in sensitivity to exposure to 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD) and other DLCs1213. Some previous studies have suggested that an in vitro assay system constructed using AHR expression vectors from chicken and other avian species may be a valuable tool for evaluating interspecies differences in responses to DLCs, and consequently for assessing risks for the species concerned1415161718.…”
mentioning
confidence: 99%
“…Although mammals have only a single AHR, birds have at least two AHR isoforms, AHR1 and AHR21011. Despite the evolutionary conservation of the AHR-mediated signaling pathway in birds, earlier in vitro and in vivo studies have reported large interspecies differences in sensitivity to exposure to 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD) and other DLCs1213. Some previous studies have suggested that an in vitro assay system constructed using AHR expression vectors from chicken and other avian species may be a valuable tool for evaluating interspecies differences in responses to DLCs, and consequently for assessing risks for the species concerned1415161718.…”
mentioning
confidence: 99%
“…From this result, we estimated the lowest concentration of embryonic liver Teqs that would be expected to alter CYP1A mRNA endpoints in cultured herring gull embryo hepatocytes. This threshold concentration was calculated using an avian toxic equivalency factor of 0.1 for PCB 126 (Van den Berg et al ), a factor of 6.4 describes the relationship between injected PCB 126 and lipid weight–based liver concentrations of PCB 126 in 19‐d chick embryos (Katynski ) and a species sensitivity factor of 20 to account for differences in CYP1A inducibility in herring gull and chicken hepatocyte cultures (Sanderson et al ). The 20‐fold correction factor refers to the difference in EC50 values between the most sensitive herring gull and an average chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Although porphyrin accumulation was not observed in the chicken embryo assay, a risk estimate should be made, because little information is available regarding species differences in sensitivity. The chicken embryo is not unequivocally the most sensitive species [68]. Porphyrin accumulation has been described in birds experimentally exposed to PCBs and hexachlorobenzene at concentrations as high as 500 mg/kg food [27,28], resulting in a PCB residue level of 50 μg/g liver [69].…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is strengthened by the study of Bellward et al [55], in which EROD induction was observed at levels twice those expected in the present study but without effects on hepatic porphyrins. Although to date no information is available regarding the porphyrinogenic sensitivity of the common guillemot, species do not seem to show large variability, as demonstrated by an in vitro study [68]. Therefore, guillemots are not likely to face disturbances of their heme biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%